New deep-sea species of Anobothrus (Annelida: Ampharetidae) from the Kuril-Kamchatka Trench and adjacent abyssal regions. (March 2020) - Alalykina, Inna L.; Polyakova, Neonila E.
Highlights: Three new ampharetid species are described from the abyssal and hadal NW Pacific. All new species have 3 pairs of branchiae and are characterized by unique features. Morphological and phylogenetic data provide evidence for the presence of new species. Abstract: Three new species of ampharetid polychaetes, Anobothrus auriculatus sp. nov., Anobothrus jirkovi sp. nov., and Anobothrus sonne sp. nov., collected from the abyss of the Kuril Basin of the Sea of Okhotsk, and from the abyssal and hadal Kuril-Kamchatka Trench area, NW Pacific, are described herein. The detailed descriptions with electron microscopy illustrations for the new species are presented and their differences from similar species are discussed. All the new species are characterized by the presence of 3 pairs of branchiae, and unique features: the presence of high paleal epidermal folds resembling ears, and only one abdominal neuropodia of thoracic type in A. auriculatus sp. nov.; the presence of rather prominent lower lip, and fleshy cup-shaped paleal base, dark colored in methylene blue staining in A. jirkovi sp. nov.; the presence of papillate ventral fold originating from fused SII–III segments in A. sonne sp. nov. Anobothrus auriculatus sp. nov. appears the deepest (9584 m) hadal representative of the genus Anobothrus described so far. Both morphological data and phylogenetic analysis provided the evidence for the presence of the three new species in the studied area. For the genus Anobothrus Levinsen, 1884 an identification key is given, including all valid species recognized world-wide.